GENGHIS KHAN’S UNIQUE DIPLOMACY IN CONQUERING THE TANGUT STATE (Scientific journal of the Fergana State University, 2025)
This article examines Genghis Khan’s unique diplomacy in subjugating the Tangut (Xia) state. In the early thirteenth century, the Tangut occupied a vital strategic position between Central Asia and China, controlling multiple important trade routes. Although Genghis Khan initially conducted large-scale military campaigns against the Tangut, he did not rely solely on force. By engaging in negotiations with local elites, military commanders, and officials, as well as employing strategic marriages, envoy exchanges, and economic incentives, the Mongols successfully incorporated Tangut territories with minimal resistance. This nuanced approach both reduced internal discord among the Tangut and provided lasting stability for the Mongol Empire’s territorial expansion. The article explores the interrelations between Genghis Khan’s diplomatic strategies, political maneuvering, and military operations. As a result of the Tangut conquest, the Mongols solidified their regional influence, leading to significant changes in trans-Eurasian trade routes and altering the broader political balance across Asia.